2019
DOI: 10.1016/j.cub.2019.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Value Integration during Economic Choice Is Regulated by Orbitofrontal Cortex

Abstract: Highlights d Rats show immediate changes in choice behavior following reinforcer revaluation d Direction of satiety-specific revaluation depends on the baseline food preference d Orbitofrontal inactivation disrupts behavior following reinforcer revaluation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…One possible resolution to this tension is a difference between species (either biological or in terms of experimental implementations). In rats, silencing OFC does not cause impairments on an economic choice task 21,22 . Another possible resolution is a difference between tasks.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One possible resolution to this tension is a difference between species (either biological or in terms of experimental implementations). In rats, silencing OFC does not cause impairments on an economic choice task 21,22 . Another possible resolution is a difference between tasks.…”
Section: Discussionmentioning
confidence: 91%
“…Lesion studies in primates have suggested that different subregions of OFC may selectively support learning and choosing [13][14][15] . In rodents, considerable evidence suggests that disrupting neural activity in the OFC impairs learning [16][17][18][19][20] , but it remains controversial whether this also impairs choice [21][22][23] . Recording studies in many species have revealed neural correlates of expected value in the OFC [24][25][26][27][28] , but it remains unclear whether these representations are selective for roles in learning and in choosing.…”
Section: Introductionmentioning
confidence: 99%
“…We targeted reward-related cortical and subcortical structures of non-human primates (Haber & Knutson, 2010) including the central orbitofrontal cortex (cOFC, area 13M), the medial orbitofrontal cortex, (mOFC, area 14O), the dorsal striatum (DS, caudate nucleus), and ventral striatum (VS), all of which are known to represent the neural correlate with stimulus values during economic choice behavior. To dissociate the integrative process to compute expected values from a choice process employed during economic choices (Chen & Stuphorn, 2015; Gardner et al, 2019; Yoo & Hayden, 2020), we recorded the neural activity in a non-choice situation; monkeys perceive and compute the expected values from probability and magnitude symbols. We used a recently developing mathematical approach, called state space analysis (Chen & Stuphorn, 2015; Churchland et al, 2012; Mante et al, 2013; Murray et al, 2017), to test how the expected-values computation is processed within each of the four neural population ensembles in an order of 10 āˆ’2 -second time resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In our study of the neurobiology of fear reduction, we also chose to move beyond the traditional fear circuit. Our candidate was the lateral orbitofrontal cortex (lOFC), a structure strongly linked to reward learning (e.g., Gardner et al, 2019 ; Padoa-Schioppa and Assad, 2006 ; Rich and Wallis, 2016 ). We targeted the OFC for three reasons.…”
Section: Introductionmentioning
confidence: 99%